Genetically stratified Parkinson’s disease with freezing of gait is related to specific pattern of cognitive impairment and non-motor dominant endophenotype - Pavelka, Lukas; Rawal, Rajesh; Sapienza, Stefano; Klucken, Jochen; Pauly, Claire; Satagopam, Venkata; Krüger, Rejko (Frontiers in Aging Neuroscience, 2024)
Background Freezing of gait (FOG) is an important milestone in the individual disease trajectory of people with Parkinson’s disease (PD). Based on the cognitive model of FOG etiology, the mechanism behind FOG implies higher executive dysfunction in PDFOG+. To test this model, we investigated the FOG-related phenotype and cognitive subdomains in idiopathic PD (iPD) patients without genetic variants linked to PD from the Luxembourg Parkinson’s study. Methods A cross-sectional analysis comparing iPDFOG+ (n = 118) and iPDFOG− (n = 378) individuals was performed, followed by the application of logistic regression models. Consequently, regression models were fitted for a subset of iPDFOG+ (n = 35) vs. iPDFOG− (n = 126), utilizing a detailed neuropsychological battery to assess the association between FOG and cognitive subdomains. Both regression models were adjusted for sociodemographic confounders and disease severity. Results iPDFOG+ individuals presented with more motor complications (MDS-UPDRS IV) compared to iPDFOG- individuals. Moreover, iPDFOG+ individuals exhibited a higher non-motor burden, including a higher frequency of hallucinations, higher MDS-UPDRS I scores, and more pronounced autonomic dysfunction as measured by the SCOPA-AUT. In addition, iPDFOG+ individuals showed lower sleep quality along with lower quality of life (measured by PDSS and PDQ-39, respectively). The cognitive subdomain analysis in iPDFOG+ vs. iPDFOG− indicated lower scores in Benton’s Judgment of Line Orientation test and CERAD word recognition, reflecting higher impairment in visuospatial, executive function, and memory encoding. Conclusion We determined a significant association between FOG and a clinical endophenotype of PD with higher non-motor burden. While our results supported the cognitive model of FOG, our findings point to a more widespread cortical impairment across cognitive subdomains beyond the executive domain in PDFOG+ with additional higher impairment in visuospatial function and memory encoding.